Experimental flow study of modeled regular and irregular glottal closure types - Kirmse, Clemens; Triep, Michael; Brücker, Christoph; Döllinger, Michael; Stingl, Michael (Logopedics Phoniatrics Vocology, 2010)
The present study shows the results of visualization experiments of the jet formation through a dynamic model of the human vocal folds. The model consists of two counter-rotating, 3D-shaped driven cams covered with a stretched silicone membrane. The 3D contours of the cams are a result of an optimized mapping of observed characteristic clinical vocal fold motions. The experiments are performed by using cams which produce the convex, triangular, rectangular, and concave or sand-glass regular glottis closure types. Two irregular cases are investigated: one of the convex cams is statically closed or opened. These cases cause an oscillating jet which attaches to the ventricular folds and appears to change the part of the aero-acoustic sound spectrum induced by vortices.